KEDUDUKAN PEREMPUAN DALAM HUKUM WARIS ADAT PADA SISTEM KEKERABATAN PATRILINEAL DI LAU PAKAM, KECAMATAN MARDINGDING, KABUPATEN KARO, PROVINSI SUMATRA UTARA - Adventi Ferawati Sembiring (Fakultas Hukum Universitas 17 Agustus (UNTAG) Semarang, 2018)
The position of women in the Patrilinel system in old times was different from that of boys, where in patrilineal kinship system was a kinship system that attracted the lineage of the men (father). Included in the system inherit among the people who adopted this kinship system. Where the right to inherit is a boy only. While the daughter can not inherit, because if the child is married then the girl is already the responsibility of her husband. So that the parents of the women are not responsible anymore against her daughter'sr, because the daughter already entered her husband family. As the background that has been described above, then the issues raised in the writing of this law is; How the position of women in customary law of inheritance today in Lau Pakam Village and Factors that influence the shift of the position of women in the system of inheritance in the village of Lau Pakam. This study uses empirical jurisdiction, namely the approach that emphasizes the theories of law and the rules of law relating to the cases studied and then connected with the fact that there are about factors that influence society. Specifications are descriptive analytical study intends to describe the legislation in force associated with legal theories and practice of positive law. Methods of data collection research directly into the field through interviews to the data for the primary and secondary data literature. Methods of data analysis used in this study is qualitative. After further research, the position of women is not as it used to be. Where women are entitled to inherit, but not equal in number with boys. where in its development there are factors influencing the growth of woman position. Among other things are economic, educational, social and religious factors. It is these factors that affect the current status of women in Lau Pakam village have grown to equality positions between boys and girls.